Nbs1 is required for ATR-dependent phosphorylation events - Stiff, Tom (Nature Publishing Group, 2005)
Nijmegen breakage syndrome (NBS) is characterised by microcephaly, developmental delay, characteristic facial features, immunodeficiency and radiosensitivity. Nbs1, the protein defective in NBS, functions in ataxia telangiectasia mutated protein (ATM)-dependent signalling likely facilitating ATM phosphorylation events. While NBS shares overlapping characteristics with ataxia telangiectasia, it also has features overlapping with ATR-Seckel (ATR: ataxia-telangiectasia and Rad3-related protein) syndrome, a subclass of Seckel syndrome mutated in ATR. We show that Nbs1 also facilitates ATR-dependent phosphorylation. NBS cell lines show a similar defect in ATR phosphorylation of Chk1, c-jun and p-53 in response to UV irradiation- and hydroxyurea (HU)-induced replication stalling. They are also impaired in ubiquitination of FANCD2 after HU treatment, which is ATR dependent. Following HU-induced replication arrest, NBS and ATR-Seckel cells show similarly impaired G2/M checkpoint arrest and an impaired ability to restart DNA synthesis at stalled replication forks. Moreover, NBS cells fail to retain ATR in the nucleus following HU treatment and extraction. Our findings suggest that Nbs1 functions in both ATR- and ATM-dependent signalling. We propose that the NBS clinical features represent the result of these combined defects.